INHIBITORY POTENTIAL OF SOME SYNTHETIC CINNAMIC ACID DERIVATIVES TOWARDS TYROSINASE ENZYME - Lanny Hartanti; Henry Kurnia Setiawan (Universitas Gadjah Mada, 2009)
Cinnamic acid is one of known tyrosinase inhibitors. This study investigated the inhibition of tyrosinase activity of some cinnamic acid derivatives, i.e. 4-buthoxy-cinnamic acid, 4-n-butylcinnamic acid and 4-phenylcinnamic acid. Each inhibitor used in this research had the same type of inhibition towards enzymatic activity, i.e. mixed type inhibition of competitive and non competitive type. The potential sequence of tyrosinase inhibition based on the ratio of its IC50 compared to cinnamic acid, from the lowest to the highest were 4-buthoxycinnamic acid, 4-phenylcinnamic acid and 4-n-butylcinnamic acid. Based on the obtained results of this research, it was disclosed that n-butyl substituent on para position did not increase the inhibition effect of cinnamic acid towards tyrosinase enzymatic reaction. But in the other hand, buthoxy and phenyl substituent on para position could increase the inhibition effect of cinnamic acid towards tyrosinase enzymatic reaction because buthoxy substituent increased the similarity of its structure with the substrate of enzymatic reaction while phenyl susbtituent blocked the substrate-enzyme reaction.